Designing e-learning for Mobile Application Development Course using Learning Experience Design (LXD) method - Rendratama, Wahyu Adhi; Setiawan, Arif (Universitas Muhammadiyah Ponorogo, 2025)
ICT has experienced rapid development and has had a very influential and significant impact on various fields and aspects of life, including in the world of education. One application of this technology is through the use of e-learning to support the teaching and learning process. Many educational institutions, both schools and universities, have utilized e-learning, especially during the pandemic which requires activities to be carried out at home. Although most teaching and learning activities and processes are now carried out face-to-face, the e-learning platform is still applied for activities such as exams and other learning activities. WordPress is one of the LMS platforms or open-source learning management systems that can be accessed at no cost, with features that have been provided and prepared that can be adjusted according to what the user needs. The varied model can only be used after being filled with various data from application user information to existing class divisions and subjects. Furthermore, primary data is collected, and the data needs to be processed first so that it matches the system format before it can be entered into the WordPress platform.